Multi‐Metal Nanocluster Assisted Cu‐Ga‐Sn Tri‐Doping for Enhanced Photoelectrochemical Water Splitting of BiVO4 Film. Issue 8 (26th February 2020) - Hu, Ruolin; Wang, Xiao‐Li; Zhang, Jiaxu; Hu, Dandan; Wu, Jin; Zhou, Rui; Li, Liang; Li, Mingde; Li, Dong‐Sheng; Wu, Tao
Abstract: Cu‐Ga‐Sn tri‐doped BiVO4 thin film is created by using a new multi‐metal chalcogenide molecular nanocluster as single‐source dopants. The modified BiVO4 photoanode with optimal doping amount (denoted as BiVO4 ‐CGS) shows the improved performance of photoelectrochemical (PEC) water splitting with a 220 mV cathodic shift in onset potential and photocurrent density of 2.5 mA cm −2 at 1.23 V versus reversible hydrogen electrode, which is 2.8 times higher than that of pristine BiVO4 . The enhanced catalytic activity is attributed to the increased charge carrier density, the improved charge separation efficiency and the accelerated surface oxygen evolution reaction (OER) dynamics of photoelectrodes. It is noted that the doping method applied here demonstrates an effective approach in not only avoiding the problems of uneven distribution of multi‐dopants or phase separation occurring in regular method, but also implementing in‐situ multi‐metal doping in a simple way. Abstract : A new Cu‐Ga‐Sn chalcogenide molecular nanocluster (ISC‐21‐CuGaSnS) is synthesized and purposely utilized as single‐source dopant to build Cu‐Ga‐Sn tri‐doped BiVO4 (BiVO4 ‐CGS) thin film via the electrodeposition method and post‐calcination process. BiVO4 ‐CGS shows improved photoelectrochemical water splitting performance than pristine BiVO4 .